2017
DOI: 10.12659/msm.899230
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) Evaluation for Anterior Disc Displacement of the Temporomandibular Joint

Abstract: BackgroundMagnetic resonance imaging (MRI) is the criterion standard imaging technique for visualization of the temporomandibular joint (TMJ) region, and is currently considered the optimum modality for comprehensive evaluation in patients with temporomandibular joint disorder (TMD). This study was aimed at finding the value of MRI in pre-clinical diagnosis of TMJ disc displacement.Material/MethodsPatients primarily diagnosed as having anterior disc displacement by clinical symptoms and X-ray were selected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
1
25
0
7
Order By: Relevance
“…On univariate regression, bilateral joint effusions and disc displacement were correlated with bilateral invasive treatment while bilateral condyle arthritis trended towards significance. Joint effusion and condyle arthritis both had odds ratio trends (OR) > 2, consistent with findings in the literature regarding the importance of these variables [ 7 , 12 , 17 , 19 , 20 ]. On multivariate regression, only disc recapture failed to trend towards statistical significance in both the six and twelve component regressions; however, it trended towards significance in predicting the need for any invasive treatment (p = 0.088) in the twelve component analysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On univariate regression, bilateral joint effusions and disc displacement were correlated with bilateral invasive treatment while bilateral condyle arthritis trended towards significance. Joint effusion and condyle arthritis both had odds ratio trends (OR) > 2, consistent with findings in the literature regarding the importance of these variables [ 7 , 12 , 17 , 19 , 20 ]. On multivariate regression, only disc recapture failed to trend towards statistical significance in both the six and twelve component regressions; however, it trended towards significance in predicting the need for any invasive treatment (p = 0.088) in the twelve component analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Suenaga associated pain syndromes with internal derangement, joint effusion, osteoarthritis, and bone marrow edema [15] , whereas others have focused on disc displacement and arthralgia [16] . An emphasis has also been placed on the disc-condyle relationship [17] , even irrespective of disc displacement or arthritis [18] . Especially after mandibular condyle fracture, joint effusion has been used as a marker of TMJ disease severity [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Lack of disc reduction during opening may limit the range of this movement by mechanically blocking or even completely preventing translational movement in the affected joint [11]. In our study the smallest (only 18 mm) range of mandibular opening was found in the group of patients with bilateral lack of disc reduction ( Table 1).…”
Section: Discussionmentioning
confidence: 44%
“…This may be explained by the gradual traction done via guiding elastics during FT, had helped in the reduction of the displaced condylar segment with subsequent disc retraction and it was sufficient to reduce the disc in 2 cases, (26) but in GI, the reduction was abruptly performed, so prevented the disc chance for re-catching the condyle, in agree with many studies. (24,27) The key findings of this study are that closed treatment of CFs is a reliable method with high successful rate and low cost. Also, FT provided a shortened period of distress, when compared to rigid IMF.…”
Section: Discussionmentioning
confidence: 87%
“…The MRI results revealed that the trauma caused anterior disc displacement in 50% of the patients, limited anterior translation of the disc/condyle assembly in 83.3% of the patients mirror these functional disruptions, (13) but was not ascertained in other study. (24) The anterior disc displacement may occurred due to the tear of the retrodiscal tissues. (25) The MRI results at 6 months FU revealed that GII was superior to GI in regaining the normal relationship.…”
Section: Discussionmentioning
confidence: 99%